RI 9528 - Evaluation Of The Three-Phase, Electric Arc Melting Furnace For Treatment Of Simulated, Thermally Oxidized Radioactive And Mixed Wastes (In Two Parts) - 1. Design Criteria and Description of Integrated Waste Treatment Facility - L. L. Oden (The National Institute for Occupational Safety and Health (NIOSH), 2010)
The U.S. Bureau of Mines and the Department of Energy (DOE), through its contractor EG&G Idaho Inc., are collaborating on a multiyear research project to evaluate the applicability of three-phase, electric arc furnace melting technology to vitrify materials simulating low-level radioactive and mixed wastes buried or stored at the Idaho National Engineering Laboratory and other DOE sites. The melter is a sealed, 1-t (1.1-st), three-phase, 800-kV?A electric arc melting furnace with 10.2-cm-(4-in?) diameter graphite electrodes, water-cooled roof and sidewalls, and four water-cooled feed tubes. A water-cooled copper fixture provides for continuous tapping of slag. An instrumented air pollution control system (APCS) with access ports for analysis and a feeder based on screw conveyors and a bucket elevator are dedicated to the facility. Test data are provided by an arc furnace analyzer and by sensors indicating feed rate; slag temperature; and temperature, pressure, and velocity in the APCS. These data are received by a data logger, digitized, and transmitted to a personal computer for storage and display. This unique waste treatment facility is available for public and private use on a cost-sharing basis.